Modernist Goods : Primitivism, the Market and the Gift. - Willmott, Glenn (University of Toronto Press, 2008)
Modernist Goods examines such writers as Yeats, Conrad, Eliot, Woolf, Beckett, H.D., and Joyce to uncover what the author views as their displaced aboriginality and to investigate the relationship between literary modernism and aboriginal modernity.